Is voting for a cartel a sign of cooperativeness? - Joris Gillet (Games, 2021)
This paper tests the hypothesis that a (partial) reason why cartels - collective but costly and non-binding price agreements - lead to higher prices in a Bertrand oligopoly could be because of a selection effect: decision-makers who are willing to form price agreements are more likely to be less competitive and pick higher prices in general. To test this hypothesis we run an experiment where participants play two consecutive Bertrand pricing games: first a standard version without the opportunity to form agreements; followed by a version where participants can vote whether to have a (costly) non-binding agreement as a group to pick the highest number. We find no statistically significant difference between the numbers picked in the first game by participants who vote for and against an agreement in the second game. We do confirm that having a non-binding agreement to cooperate leads to higher numbers being picked on average. Both participants who voted for and against the agreement increase the number they pick in situations with an agreement. However, this effect is bigger for participants who voted in favour.
Keywords: C91; D02; D43; L13; 330; experimental economics; non-binding promise; oligopoly; social dilemma